Étude sur les besoins spécifiques des femmes immigrantes francophones en situation minoritaire - Alliance des femmes de la francophonie canadienne (L’Alliance des femmes de la francophonie canadienne (AFFC), 2021)

Healthcare Access of Autistic Language Minorities: The Case of English Official Language Minorities in Quebec, Canada - Amantayev, Nariman; Rao, Sabrina; Nadig, Aparna (Minorités linguistiques et société, 2025)
Abstract English and French are both official languages in Canada. Whereas official language minorities (English speakers in Quebec, French speakers in the rest of Canada) face healthcare barriers and poor health outcomes, autistic individuals and their families also struggle with accessing healthcare. We examined healthcare access at the intersection of these groups: the autistic community, including English minority-language speakers from Quebec, French majority-language speakers from Quebec, and English majority-language speakers from elsewhere in Canada (n = 165). Linguistic minorities reported poorer access to publicly-funded services and lower satisfaction that their language needs were being met than did linguistic majorities. Foreign-born English speakers also experienced poorer access than their Canadian-born counterparts. These preliminary findings suggest that autistic language minorities face known barriers to accessing healthcare, potentially at a higher rate than that experienced by language minorities in general. Résumé L’anglais et le français sont les langues officielles du Canada. Les minorités de langue officielle (anglophones au Québec, francophones hors Québec) font face à des obstacles en matière de santé, tout comme les personnes autistes et leurs familles. Nous avons examiné l’accès aux services de santé à l’intersection de ces groupes : la communauté autiste, incluant des anglophones (minoritaires) et francophones (majoritaires) du Québec, ainsi que des anglophones (majoritaires) du reste du Canada (n = 165). Les minorités linguistiques déclarent un accès plus difficile aux services de santé publics et une moindre satisfaction quant à la prise en compte de leurs besoins linguistiques, comparativement aux majorités linguistiques. Les anglophones nés à l’étranger rapportent également un accès plus difficile que leurs pairs nés au Canada. Ces résultats préliminaires suggèrent que les minorités linguistiques autistes font face à des obstacles connus en matière d’accès aux soins, possiblement à un degré plus élevé.

Évaluation de l’offre active des services de santé de première ligne - Comité santé en français de Fredericton (Groupe Progecom communication et stratégies d’entreprise, 2006)

Bien dans notre peau: Élaboration d’un outil de diagnostic pour informer la conception et l’évaluation de services et partenariats sécuritaires, inclusifs et équitables pour toute personne 2ELGBTQ+ d’expression française au Manitoba - Courcelles, Rémi; Hardy, Stephan; Prada, Kevin (Santé Canada, 2023)

Améliorer l’accès des personnes âgées de Saint-Boniface et de Saint-Vital aux services de santé en français. Objectif 2 – Inventaire des services de santé disponibles en français et identification des déficits de services - De Moissac, Danielle; Ba, Halimatou; Gagné, Maryanne; Éthier, Sophie (Conseil communauté en santé du Manitoba, 2012)
Au Manitoba, des services de santé en français sont disponibles à Winnipeg, et plus précisément à Saint-Boniface et à Saint-Vital, où habite une forte concentration de francophones. L’objectif de ce deuxième volet de recherche sur l’accès des personnes âgées aux services de santé en français est de dresser un inventaire représentatif des services de santé publics, privés à but lucratif, privés à but non lucratif ou communautaires disponibles en français dans ces deux quartiers, pour ensuite identifier les déficits de services. On définit ici la disponibilité comme étant un service dont peuvent disposer les aînés et qui peut être utilisé par quiconque en fait la demande. Cet inventaire permettra de mieux connaître le nombre, le type et la nature des services existants et de déterminer si tous les services de santé et services sociaux disponibles en français sont répertoriés, soit dans l’Annuaire des services en français de la Société franco-manitobaine. Ceci est important, car une plus grande visibilité des services disponibles en français contribue grandement à leur utilisation par les aînés francophones et leurs aidants lorsque le besoin survient. De plus, l’inventaire permettra d’identifier le type et la nature des services manquants auxquels la population vieillissante pourrait avoir recours.

Healthcare Service Utilization and Perceived Gaps: The Experience of French-Speaking 2S/LGBTQI+ People in Manitoba - de Moissac, Danielle; Prada, Kevin; Gueye, Ndeye Rokhaya; Avanthay-Strus, Jacqueline; Hardy, Stephan (Healthcare Policy, 2024)
Ethnolinguistically diverse 2S/LGBTQI+ (two-spirit, lesbian, gay, bisexual, transgender, queer and intersex) populations have unique healthcare needs and experience health inequities compared to their cisgender or heterosexual peers. This community-based participatory study sought to describe the profile and healthcare needs and experiences of official language minority French-speaking 2S/LGBTQI+ adults in Manitoba. Participants (N = 80) reported that gender and sexual identity were often concealed from service providers; many respondents faced discrimination based on their ethnolinguistic and sexual identities. Service gaps are identified pertaining to mental and sexual health; locating 2S/LGBTQI+-friendly, patient-centred care in French is difficult. Policy and practice should address systemic inequity and discrimination experienced by this equity-seeking population.

‘It would be nice if they could give us more language’ – Serving South Africa’s multilingual patient base - Deumert, Ana (Social Science & Medicine, 2010)

Pas de problème: Rapport du comité d'action sur les services de santé en langue française, 1976 - Dubois, Jacques (Ministère de la santé, Ontario, 1976)
Ce rapport est le fruit des travaux du Comité d'action sur les services de santé en langue française, institué par le ministère de la Santé de l'Ontario et officialisé par un arrêté-en-conseil approuvé en février 1975. Le titre "Pas de problème" est choisi parce que selon le comité, il "résume assez bien la réponse des resposnables de services de santé qui n'ont pas encore perçu les besoins d'un groupe linguistique minoritaire. Pas de problème. Cette simplification d'une situation pourtant très complexe dénote sans doute l'attitude que rencontre trop souvent la population française de l'Ontario." Après une brève recension d'écrits (majoritairement américains) sur les barrières linguistiques en santé, le rapport fait un état des lieux en Ontario à cette époque et énonce plus d'une centaine de recommandations.

Services de santé dans la langue officielle du patient : liens avec la proximité, la région et les facteurs sociodémographiques - Fernandes, Daphné (Regards sur la société canadienne, 2025)
À l’aide des données tirées de l’Enquête sur la population de langue officielle en situation minoritaire de 2022 et de la Base de données ouverte sur les établissements de soins de santé, la présente étude examine l’incidence de la proximité des établissements de santé, et d’autres facteurs régionaux et sociodémographiques, sur l’accès à des soins dans la langue de choix de la population de langue officielle en situation minoritaire au Canada. Dans cet article, les soins en concordance linguistique se rapportent aux personnes qui reçoivent des services de santé dans la langue officielle de leur choix (français ou anglais). L’analyse porte sur les adultes de 18 ans et plus vivant dans différentes régions du Canada.

Health services in a patient’s own official language: Associations with proximity, region and sociodemographic factors - Fernandes, Daphné (Insights on Canadian Society, 2025)
Using data from the 2022 Survey on the Official Language Minority Population and the Open Database of Healthcare Facilities, this study examines how distance to health care facilities, alongside regional and sociodemographic factors, relates to access to language-concordant care for the official language minority population in Canada. In this article, language-concordant care refers to individuals receiving health care services in their preferred official language (English or French). The analysis focuses on adults aged 18 and older living across Canada.

Language barriers and healthcare access: a qualitative study in the Volta Region of Ghana - Glover-Meni, Nathaniel; Nyarko, Joy Ato; Agbezorlie, Peter K.; Agyei, Dominic Dankwah (Journal of Communication in Healthcare, 2024)
Background The study explores the language barriers between two language minority populations and healthcare professionals in the Volta Region of Ghana. Methods An interpretive description with a qualitative approach to data collection and analysis was used. This study was carried out in the Tafi-Atome and Avatime-Vane communities, the Hohoe Municipal Hospital and the Margaret Marquart Catholic Hospital in the Kpando Municipality. In all, 46 respondents comprising 19 purposively sampled community members (patients) from the two selected communities and 27 conveniently sampled healthcare professionals from the two health facilities were interviewed. The face-to-face in-depth interviews were audio-recorded, transcribed and thematically analysed. Results The study revealed a barrier in language use between healthcare professionals and patients from the two language minority communities. While healthcare professionals preferred to use English, Akan and Ewe, the patients, on the other hand, preferred their native languages, which are Sideme and Tegbor. The services of unqualified interpreters were utilised by both healthcare professionals and patients. Study participants were aware of these challenges, which prevented the patients from receiving optimum healthcare services, and the healthcare workers from delivering client-centred healthcare services. Conclusions The presence of communication challenges emanating from language barriers between healthcare professionals and patients should be considered as a key hindrance to the attainment of the Sustainable Development Goal Three (SDG3), which aims to promote health and well-being at all ages. Therefore, stakeholders in the healthcare delivery system in Ghana need to prioritize stronger communication and translation practices and policies.

Ma santé, en français s'il vous plaît ! Une proposition qui traite des besoins des franco-ontariens et des franco-ontariennes de Thunder Bay en ce qui a trait aux soins de santé primaires - Larouche, Jérémie (Association des Francophones du Nord-Ouest de l'Ontario, L'Accueil francophone de Thunder Bay, Réseau francophone de santé du Nord de l'Ontario, 2007)

« Bâtir sur les fondations - améliorer les résultats pour la santé et accroître la vitalité des communautés anglophones du Québec ». Rapport présenté au ministre fédéral de la santé - Nouvet, Marcel; Maldoff, Eric (Comité consultatif des communautés anglophones en situation minoritaire, 2007)

“Building on the foundations, working toward better health outcomes and improved vitality of Quebec's English-speaking communities”. Report to the Federal Minister of Health - Nouvet, Marcel; Maldoff, Eric (Consultative Commitee for English-Speaking Minority Communities, 2007)

Argumentaire pour la promotion d’une offre de service santé de qualité dans la langue maternelle des clients au Nunavut - Réseau Santé en français au Nunavut (2021)

Des services de santé en français dans un Nord en mutation. Un défi intercommunautaire - Réseau Santé en français au Nunavut (Association des Francophones du Nunavut, Santé en français au Nunavut, 2006)

À la rencontre des communautés acadiennes et francophones et de leurs enjeux en santé - Réseau Santé Nouvelle Écosse (Réseau santé en français de Nouvelle-Écosse, 2021)

Pratique # 12 : Les Lunchs-causeries au Centre de services communautaires Vanier (Ontario) - Savard, Jacinthe; Savard, Sébastien; van Kemenade, Solange; Benoît, Josée; Buhay, Corrina; Youbi, Sara; Kubina, Lucy-Ann (2021)

Pratique # 13 : Une infirmière de Santé publique dans un centre de services communautaires qui assure l’aiguillage des aînés (Ontario) - Savard, Jacinthe; Savard, Sébastien; van Kemenade, Solange; Benoît, Josée; Buhay, Corrina; Youbi, Sara; Kubina, Lucy-Ann (2021)

Pratique # 14 : Les Foires d’information de la Fédération des aînés et des retraités francophones de l’Ontario (FARFO) - Savard, Jacinthe; Savard, Sébastien; van Kemenade, Solange; Benoît, Josée; Buhay, Corrina; Youbi, Sara; Kubina, Lucy-Ann (2021)

Pratique # 9 : Les Soins primaires communautaires pour aînés (Primary Care Outreach to Seniors) (Ontario) - Savard, Jacinthe; Savard, Sébastien; van Kemenade, Solange; Benoît, Josée; Buhay, Corrina; Youbi, Sara; Kubina, Lucy-Ann (2019)

The effects of a language barrier in a South African district hospital - Schlemmer, A.; Mash, B. (South African Medical Journal = Suid-Afrikaanse Tydskrif Vir Geneeskunde, 2006)
BACKGROUND: Communication between health workers and patients at Hottentots Holland Hospital (HHH) is hindered by staff and patients not speaking the same language. HHH is a district hospital in the Cape Town Metropolitan District of the Western Cape where staff mainly speak Afrikaans or English and a large number of patients mainly Xhosa. OBJECTIVES: The study aimed to explore the effects of this language barrier on health workers and patients at HHH. DESIGN: Three focus group interviews were held with 21 members of staff and 5 in-depth patient interviews were conducted. RESULTS: The language barrier was found to interfere with working efficiently, create uncertainty about the accuracy of interpretation, be enhanced by a lack of education or training, cause significant ethical dilemmas, negatively influence the attitudes of patients and staff towards each other, decrease the quality of and satisfaction with care, and cause cross-cultural misunderstandings. CONCLUSION: The effects of the language barrier were considerable and persistent despite an official language policy in the province. The training and employment of professional interpreters as well as teaching of basic Xhosa to staff are recommended.
Keywords: Communication Barriers; Health Services Accessibility; Hospitals, District; Humans; Language; Multilingualism; Outcome Assessment, Health Care; Professional-Patient Relations; South Africa; Surveys and Questionnaires

Agir ensemble pour une Petite enfance en santé dans les communautés francophones et acadienne en situation minoritaire : Résultats et impacts du programme Petite enfance en santé 2024-2025 - Société Santé en français et les Réseaux de santé en français (2025)

The pharmacist is in: The availability and distribution of French-speaking pharmacists in Ontario - Timony, Patrick E.; Waite, Nancy; Houle, Sherilyn; Violette, Richard; Gauthier, Alain P. (Linguistic Minorities and Society, 2022)
Francophones are an official language minority in Ontario with limited access to linguistically concordant healthcare services. Although communication is an important skill in the field of pharmacy, little is known about the availability of French-speaking pharmacists. This secondary data analysis of the Ontario College of Pharmacists registry converted weekly hours worked into full-time equivalents (FTEs) and calculated ratios of pharmacist FTEs per 1,000 population. French-speaking pharmacists tended to offer fewer FTEs in communities with a larger concentration of Francophones, particularly in northern and rural areas, a trend that was not observed among English-speaking pharmacists. This maldistribution of French-speaking pharmacists may limit the ability of official language minority patients to receive pharmacy services in their language of choice. Keywords: English, pharmacists, Francophones, linguistic concordance, geographic distribution, French-language health services

Pratique # 27 : Accueil centralisé (Centre francophone du Grand Toronto, Ontario) - van Kemenade, Solange; Benoît, Josée; Savard, Sébastien; Savard, Jacinthe (2025)

Pratique # 23 : Navigateur francophone du système de santé (Terre-Neuve-et-Labrador) - van Kemenade, Solange; Michel, Jean Nephetaly; Savard, Jacinthe; Benoît, Josée (2021)

Access to healthcare services and confidence in healthcare professionals’ management of malaria: the views of Francophone sub-Saharan African Immigrants living in western Canada - Vincent, Rémi; Coulibaly, Kongnon Sangué; Ahmed, Ali; Ahmed, Youssef; Hanna, Taylor A.; Ravi, Srilata; Hawkes, Michael T.; Gnidehou, Sedami (BMC Public Health, 2023)
Abstract Background There is a paucity of knowledge about the healthcare attitudes and practices of French-speaking immigrants originating from Sub-Saharan Africa (FISSA) living in minority settings. The purpose of this study was to characterize FISSA healthcare experiences and confidence in the malaria-related knowledge of health professionals in Edmonton. Methods A structured survey was used to examine a cohort of 382 FISSA (48% female; 52% male) living in Edmonton. FISSA general healthcare attitudes, experiences and satisfaction with the Canadian healthcare system were studied. Healthcare Competency Perception (HCP) was characterized by using an index score. Statistical analyses were performed to evaluate the impact of healthcare experiences and other outcomes. Results Intriguingly, while only 42% of FISSA had a French-speaking family physician, 83% (197/238) of those who had received health care services in Alberta found that access to medical treatment was easy, and 77% (188/243) were satisfied with received care. Although 70% (171/243) of FISSA did not receive services in French, 82% (199/243) surprisingly reported having good levels of comprehension during their visits. Satisfaction with care was associated with having a family physician (p = 0.018) and having health insurance (p= 0.041). Nevertheless, confidence in the healthcare system’s ability to treat malaria effectively was significantly lower, with only 39% (148/382) receiving a positive score on the HCP index. Conclusion This study provides an important insight into FISSA experience with and perception of the Alberta’s healthcare system.